Implementasi Pelaksanaan Administrasi Perceraian Secara Elektronik Melalui E-Court Dalam Upaya Peningkatan Pelayanan Publik Di Pengadilan Agama Pekanbaru Kelas 1A - Hayatina, Nursri; Pivit Septiary Chandra (Jurusan Administrasi Publik, FISIP, Universitas Sriwijaya, 2023)
The Pekanbaru Class 1A Religious Court is a judicial body under the auspices of the Supreme Court which has carried out the implementation of electronic divorce administration